Az Europai Unio fejlesztesi forrasai felhasznalasanak ertekelese a regionalis operativ programok kereteben (Evaluation of Using EU Funding Sources in the Regional Operational Programmes) - Éva Pálmai (DETUROPE)
Cohesion policy should continue to play a critical role in these difficult times – when Europe need to exit from a deep crisis and reduce unemployment and poverty, while switching to a low-carbon economy – in order to deliver smart, sustainable and inclusive growth, while promoting harmonious development of the Union and its regions by reducing regional disparities. According to most of the reports have been created for the European Commission cohesion policy has made a significant contribution to spreading growth and prosperity across the Union, while reducing economic, social and territorial disparities. The aim of this study is to identify the results of the efforts of the cohesion policy in the field of reducing territorial disparities: the connection between the social, economic development of the Hungarian regions and the capacity of receiving funding from the Regional Operational Programmes. As for conclusion of this study for the period 2007-2011, it follows the resource allocation system supported both increasing competitiveness of the developed regions and catching up the less developed regions by reducing regional disparities.